Історичні витоки української державності - Капуста, Р. Д. (ХНУРЕ, 2020)
In this article, I will try to show the relevance of this topic, exactly the study of the origins of the Ukrainian state and draw an analogy with the modern development of history. Here will be told about the development of cultural values and their reflection in everyday realities. The religious and everyday features of the Cossack life are also affected. Історія України – це фактично історія національно-визвольної боротьби українського народу за свою державу. Цей рух був спрямований на визволення народу з-під іноземного панування та здобуття національної державної незалежності.
Keywords: культурне розмаїття; українознавство; традиції; культура